THE IMPORTANCE OF MIGRATION IN THE INTEGRATION OF CULTURAL RELATIONS - Halimov Sherzod Igamberdiyevich (Galaxy International Interdisciplinary Research Journal, 2024)
This article analyzes the essence of human cultural existence, material and spiritual culture. It happens as a result of the development of personal cultural relations, interaction and integration with other peoples. The integration of mutual cultural values between peoples appears as a result of mihration.